2022
DOI: 10.1038/s41380-022-01518-6
|View full text |Cite
|
Sign up to set email alerts
|

Aβ profiles generated by Alzheimer’s disease causing PSEN1 variants determine the pathogenicity of the mutation and predict age at disease onset

Abstract: Familial Alzheimer’s disease (FAD), caused by mutations in Presenilin (PSEN1/2) and Amyloid Precursor Protein (APP) genes, is associated with an early age at onset (AAO) of symptoms. AAO is relatively consistent within families and between carriers of the same mutations, but differs markedly between individuals carrying different mutations. Gaining a mechanistic understanding of why certain mutations manifest several decades earlier than others is extremely important in elucidating the foundations of pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 66 publications
11
67
0
Order By: Relevance
“…Pathogenic variants causing early‐onset, autosomal dominant AD shift Aβ production toward the generation of longer and aggregation‐prone peptides (Chávez‐Gutiérrez et al , 2012; Fernandez et al , 2014; Kretner et al , 2016; Veugelen et al , 2016; Liu et al , 2022), and the mutation‐driven increments in these longer Aβ forms (≥ 42 aa) show a linear correlation with clinical onset (Petit et al , 2022). This observation strongly supports the therapeutic value of strategies aimed at lowering the levels of longer Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic variants causing early‐onset, autosomal dominant AD shift Aβ production toward the generation of longer and aggregation‐prone peptides (Chávez‐Gutiérrez et al , 2012; Fernandez et al , 2014; Kretner et al , 2016; Veugelen et al , 2016; Liu et al , 2022), and the mutation‐driven increments in these longer Aβ forms (≥ 42 aa) show a linear correlation with clinical onset (Petit et al , 2022). This observation strongly supports the therapeutic value of strategies aimed at lowering the levels of longer Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the more the mutation undermines E‐S interactions, the earlier the disease manifests. In fact, the molecular composition of FAD‐linked Aβ profiles not only informs about pathogenicity, but also enables the estimation of age at disease onset (Petit et al , 2022). These findings strongly support the notion that the stabilization of GSEC‐APP/Aβ n interactions, and consequent shift in Aβ production toward shorter and soluble Aβ peptides, may serve as a therapeutic strategy to tackle early, Aβ‐driven pathogenic cascades in FAD, and broadly in the most common, late‐onset SAD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies that investigated potential relationships between the molecular composition of FAD-linked Aβ profiles and disease severity by analyzing Aβ profiles generated by 25 mutant PSEN1/GSECs that span a wide range of AAOs, revealed that full spectrum of Aβ profiles (including Aβ37, Aβ38, Aβ40, Aβ42, and Aβ43) better reflects mutation pathogenicity. Furthermore, this study suggested Aβ(37 + 38 + 40)/Aβ(42 + 43) ratio better at predicting the age at disease onset (Petit et al, 2022). Presently, PSEN1 gene is considered as the most common cause of familial Alzheimer's disease (FAD).…”
Section: Presenilinmentioning
confidence: 77%
“…To quantify γ-secretase processivity, Chávez-Gutiérrez's lab has introduced a ratio between the sum of the products of the 4th catalytic turnover divided by the sum of the products of the 3rd catalytic step, which are the substrates of the 4th catalytic turnover [9]. Ultimately, this ratio provides an overall measure of γsecretase processivity along both product lines.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, this ratio provides an overall measure of γsecretase processivity along both product lines. Applying this method to an in vitro analysis of Aβ pro les of 25 FAD-linked PSEN1 mutants, the authors found a linear correlation between mutation-driven alterations in Aβ pro les and age at onset of AD in humans [9]. Hence, to assess γ-secretase processivity in our 9 rat lines we calculated the Aβ (38 + 40)/(42 + 43) ratios.…”
Section: Resultsmentioning
confidence: 99%